Main research areas in kickboxing investigations: an analysis of the scientific articles of the Web of Science Core Collection - Podrigalo, L. V.; Shi, K.; Podrihalo, O. O.; Volodchenko, O. A.; Halashko, O. I. (Pedagogy of Physical Culture and Sports, 2022)
Background and Study Aim. Combat sports are among the most popular sports nowadays. Scientific support of combat sports is one of the urgent tasks of modern sports science. The purpose of this article is an analytical analysis of studies devoted to kickboxing.